2002
DOI: 10.1002/jcb.10145
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor and thrombin induced proliferation of immortalized human keratinocytes is coupled to the synthesis of Egr‐1, a zinc finger transcriptional regulator

Abstract: The epidermal growth factor (EGF) receptor is highly expressed in HaCaT keratinocytes as shown by Western blotting. Stimulation of HaCaT cells with EGF, and also with the serine protease thrombin, induced DNA synthesis, measured by incorporation of 5-bromo-2'-deoxyuridine into the DNA of proliferating cells. Using antibodies directed against the active form of the EGF receptor, we show that in HaCaT cells EGF and thrombin triggered a rapid activation of the EGF receptor, followed by the phosphorylation and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
3
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 49 publications
4
100
3
1
Order By: Relevance
“…These results suggest that egr-4 is expressed in two distinct phases during regeneration, an early, Smed-egfr-3-independent, phase, and a subsequent phase that is controlled by EGFR signaling. These findings are supported by previous studies demonstrating that the expression of egr genes is regulated by the EGFR pathway in different organisms and contexts (Kaufmann and Thiel, 2002;Tsai et al, 2000, Lindzen et al, 2012.…”
Section: Egr-4 Rnai Disrupts Head Regeneration Without Impairing the supporting
confidence: 89%
“…These results suggest that egr-4 is expressed in two distinct phases during regeneration, an early, Smed-egfr-3-independent, phase, and a subsequent phase that is controlled by EGFR signaling. These findings are supported by previous studies demonstrating that the expression of egr genes is regulated by the EGFR pathway in different organisms and contexts (Kaufmann and Thiel, 2002;Tsai et al, 2000, Lindzen et al, 2012.…”
Section: Egr-4 Rnai Disrupts Head Regeneration Without Impairing the supporting
confidence: 89%
“…Up-regulation of EGR1 expression may result in apparently contradictory activities including mitogenesis (33,34), differentiation (35,36), tumor suppression (37), apoptosis, and protection from apoptosis (38,39). It was suggested that EGR1 exerts its activity by regulating the expression of different genes involved in various pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on glioma cells (Kaufmann and Thiel, 2001) following EGF stimulation indicated that hEGR1 may be an important part of the EGF-initiated signalling cascades and showed that hEGR1 gene transcripts and protein were undetectable in the absence of cell stimulation by EGF. A similar proposal that hEGR1 may be an important late part of the EGF signalling cascade is reported in a study of EGF and thrombin on keratinocytes (Kaufmann and Thiel, 2002). EGF induced a transient synthesis of hEGR1 with a peak between 1 and 5 h. Proliferation, activation of ERK and biosynthesis of hEGR1 was inhibited by AG1487, an EGFR specific tyrosine kinase inhibitor.…”
Section: Discussionsupporting
confidence: 78%